Bilevel programming problems : theory, algorithms and applications to energy networks /: theory, algorithms and applications to energy networks. ([2015]) - Dempe, Stephan; Kalashnikov, V. V (Vyacheslav V.); Pérez-Valdés, Gerardo A; Kalashnykova, Nataliya
No abstract available